P316 A pilot consequences of colorectal cancer virtual clinic in lincolnshire during the COVID-19 pandemic. (19th June 2022) - Fernandes, Darren; Andreyev, Jervoise
Abstract : Introduction: Recent reductions in cancer mortality rates are the result of better screening and the use of improved treatments. Whilst there has been a longstanding awareness of the psychological and social impact of cancer therapy, there has been little emphasis on dealing with the physical symptoms that are a frequent complication of treatment. This can include living with chronic and debilitating bowel symptoms as well as problems with sexual and urinary function. At the United Lincolnshire Hospitals Trust, over 400 patients are diagnosed and treated for colorectal cancer annually. We therefore sought to develop a unique virtual service to help patients who have developed gastrointestinal symptoms following treatment. Methods: A virtual telephone clinic was set up during the COVID-19 pandemic. Patients in need of specialist gastroenterology input were identified by CRC nurse specialists, colorectal surgeons or oncology specialists in their follow up clinics. Patients were then reviewed by a gastroenterology research fellow via a telephone consultation. Investigations requested included blood tests, faecal elastase, faecal calprotectin, SeHCAT scan, abdominal x-ray and breath test. Results: 38 patients (18 male, 20 female) were reviewed between October 2020 to October 2021. The median age was 71 (range 44 to 86) and the average duration of symptoms was 38 months (range 8 to 86). The site of cancer was in 22 rectum, 6 sigmoid colon, 1 transverse colon, 3 ascending colon and 6 caecum. All had been diagnosed with CRC and received treatment that included surgery, chemotherapy, radiotherapy either alone or in combination with one another. Symptoms included loose stool, bloating, increased frequency and incontinence with diagnoses made shown in Chart 1. Patients' symptoms pre-referral and post treatment were assessed objectively using the gastrointestinal symptoms rating scale (GSRS), with an average GSRS on referral of 29.5, improving to 16.2 following investigation and treatment. Conclusions: In most patients referred to our specialist clinic, we have been able to identify one or more cause for their problems. Treatment, that may include laxatives, bile acid sequestrants, antibiotics and dietary changes may lead to a dramatic improvement in symptoms. Future recommendations include earlier recognisation of patients in need of specialist referral through the use of symptom questionnaires, improved funding for this neglected field in post cancer treatment and the development of similar consequences of cancer clinics in trusts nationwide.